2004
DOI: 10.2105/ajph.94.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors for Adult and Child Hunger Among Low-Income Housed and Homeless Female-Headed Families

Abstract: This study found that the odds of hunger, although affected by resource constraints in low-income female-headed families, were also worsened by mothers' poor physical and mental health. Eliminating hunger thus may require broader interventions than food programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
76
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 35 publications
5
76
0
Order By: Relevance
“…This is also implied by the screening procedures for subsidized housing in Toronto whereby housing authorities prioritize particularly disadvantaged households such as homeless people, youths, and families separated because of lack of housing, 43 and in previous US research with low-income femaleheaded households that found a positive association between receipt of housing subsidies and child hunger. 44 We endeavored to account for a selection effect by including potential sociodemographic confounders in our model and repeating the analysis including only those market households on a waiting list for subsidized housing. Although longitudinal data are needed to understand the impact of moving into subsidized housing on food security, the lower odds of food insecurity among families in subsidized housing compared to those on the waiting list implies that subsidies afford some advantage.…”
Section: Discussionmentioning
confidence: 99%
“…This is also implied by the screening procedures for subsidized housing in Toronto whereby housing authorities prioritize particularly disadvantaged households such as homeless people, youths, and families separated because of lack of housing, 43 and in previous US research with low-income femaleheaded households that found a positive association between receipt of housing subsidies and child hunger. 44 We endeavored to account for a selection effect by including potential sociodemographic confounders in our model and repeating the analysis including only those market households on a waiting list for subsidized housing. Although longitudinal data are needed to understand the impact of moving into subsidized housing on food security, the lower odds of food insecurity among families in subsidized housing compared to those on the waiting list implies that subsidies afford some advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the effects of participation in food assistance programmes have resulted in inconsistent findings (19)(20)(21)23,25,28,29,40) . In the present cross-sectional study, the association between food insecurity and participation in food assistance programmes was weak and not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In the present cross-sectional study, the association between food insecurity and participation in food assistance programmes was weak and not statistically significant. One reason could be that the research design was not able to control for self-selection of more food-needy households into the programme, leading to weakened effects of the programmes (19)(20)(21)29) . Several studies suggested that participation in programmes can be coincident with food insecurity rather than factors that contribute to or protect against food insecurity (21,50) .…”
Section: Discussionmentioning
confidence: 99%
“…26,27 In the limited existing examination of this issue, Melchior and colleagues 28 and Wehler and colleagues 29 found higher rates of IPV among female-headed families experiencing food insecurity compared to those not experiencing food insecurity. Similarly, more recent research on female-headed households indicates that childhood trauma and violence are also associated with experiencing very low food security during adulthood.…”
Section: Intimate Partner Violence and Maternal Depressionmentioning
confidence: 99%
“…33 Other research has suggested that the quality and quantity of food purchases among food insecure households are based on the sense financial security. 34 However, Wehler and colleagues 29 propose that the managerial strategies used to avoid hunger (also including providing the necessary time and attention to the task of acquiring food) may be hampered among mothers who experience IPV, placing the entire household at risk for experiencing food insecurity. We propose that the experience of depression among victims of IPV may be a mechanism accounting for their apparent impaired ability to obtain adequate food, resulting in the household to experience food insecurity.…”
Section: Intimate Partner Violence and Maternal Depressionmentioning
confidence: 99%